Proposição de um modelo de balanced scorecard para uma Instituição Privada de Ensino Superior - Yasui, Angelo Toyokiti (2019)
The educational sector has undergone great transformations since 1996 with the promulgation of the law of guidelines and bases of education. Over the years, a new dynamic of competition between higher education institutions is evidenced mainly with the advent of capital inflows of large investors in the sector. The supply of vacancies increases while there is a greater difficulty in occupying them. The education sector becomes more competitive and institutions are required to improve their management model. In this context, the objective of this work is to propose a balanced scorecard model for a private institution of higher education, using as a methodological procedure interventionist research with a collaborative approach. A review of the literature on the BSC models already implanted in higher education institutions that supported the interactions with the members of the institution was carried out. The results analysis allows to highlight the proposition of the BSC model, as well as significant impacts of the intervention in the management of the institution, such as the rescue of the strategic ambitions, the creation of a management committee, the greater sharing of information and the awareness of the owner of the institution on the importance of having a tool that provides the execution of the strategy. It can be inferred that this work brings as a contribution the possibility of using the BSC even in institutions that do not have pre-established monetary performance indicators, adopting as main strand the establishment of leading indicators. The proposed BSC model becomes a reference for implementation in other higher education institutions.